1971
DOI: 10.1002/macp.1971.021420111
|View full text |Cite
|
Sign up to set email alerts
|

Free radicals in diene polymers induced by ultraviolet irradiation. II. An ESR study of cis‐1.4‐poly(butadiene)

Abstract: Radical formation was observed in purified ois-1.4-poly(butadiene) after irradiation in vucuo at 77'K with UV light from a medium pressure mercury lamp. The free radicals were studied by electron spin resonance (ESR). The ESR spectra obtained were interpreted as due mainly to radicals formed by scission of the C-C bond midway between the double bonds : 0 -CHz-CH=CH-HZ t-+ -CH2-CH-CH=CHz A minor part was assigned to radicals formed by hydrogen abstraction from one of the a-methylene groups. These radicals are b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…If so, the ESR signal from allyl radical should show a clear hyperfine splitting [16,35,36]. Carstensen reported that the allyl radicals in polybutadiene and polyisoprene formed at liquid nitrogen temperature were easily transformed into polyenyl radical (-(CaC) n -C%) during heating [35,36]. In addition, the g-value and DH msl for polyenyl radical are reported to be 2.004 and 1.6 mT [35,37].…”
Section: Esr Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…If so, the ESR signal from allyl radical should show a clear hyperfine splitting [16,35,36]. Carstensen reported that the allyl radicals in polybutadiene and polyisoprene formed at liquid nitrogen temperature were easily transformed into polyenyl radical (-(CaC) n -C%) during heating [35,36]. In addition, the g-value and DH msl for polyenyl radical are reported to be 2.004 and 1.6 mT [35,37].…”
Section: Esr Resultsmentioning
confidence: 94%
“…Thus, the allyl radical (-CaC-C%) is likely to be formed by the chain scission. If so, the ESR signal from allyl radical should show a clear hyperfine splitting [16,35,36]. Carstensen reported that the allyl radicals in polybutadiene and polyisoprene formed at liquid nitrogen temperature were easily transformed into polyenyl radical (-(CaC) n -C%) during heating [35,36].…”
Section: Esr Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This lower binding energy resulted in an easy break down of the molecular chains by heat. KEY WORDS Polyisoprene / Silica / ESR / Rubber Gel / (Received March 27, 2007: Accepted August 22,2007) [ Kobunshi Ronbunshu, 64(11), 779-785 (2007)]…”
mentioning
confidence: 99%
“…In this work, this was taken into consideration to determine the line width. As discussed in our previous paper 10) , the absorption is assigned to the polyenyl radical (-(CϭC) n -C ·) [23][24][25] formed by the chain scission during sample preparation. The intensity of ESR signals increased with increasing the strain (initial strain: IS, (Fig.…”
Section: Esr Resultsmentioning
confidence: 81%